Microstructural effect on the low temperature transport properties of Ce–Al (Ga) metallic glasses. (June 2016) - Singh, Dharmendra; Singh, Devinder; Srivastava, O.N.; Tiwari, R.S.
Abstract: The substitution of Ga in Ce75 Al25 − x Gax (x = 0 and 4 at.%) metallic glasses (MGs) has led to phase separation giving rise to nano-amorphous domains in a glassy matrix. The CeL3 -edge XAS spectra for x = 4 has shown appearance of 4f 0 delocalized states. The temperature coefficient of resistance (TCR) becomes higher with addition of Ga. The magnetic field tuned magnetoresistance (MR) transition from positive to negative values has been observed for the first time with Ga substitution. These changes in the transport properties have been discussed in terms of formation of nano-amorphous domains and its link with 4f electrons for Ce atoms. Graphical abstract: In the present work, the effect of microstructural variation on the low temperature transport properties of Ce75 Al25 − x Gax (x = 0 and 4 at.%) metallic glasses (MGs) have been investigated. The substitution of Ga has led to phase separation giving rise to nano-amorphous domains in a glassy matrix. It was suggested that the presence of two types of density clusters in the alloy with x = 4 may result in the formation of nano-amorphous domains with different short range ordering. The magnetic field tuned MR transition from positive to negative values at about 2.45 T has been observed for the first time with Ga substitution. The changes in the transport properties due to Ga substitution have been discussed in terms of formation of nano-amorphous domains and its link with 4f electrons for Ce atoms. This work, therefore, opens up new direction of investigation of 4f electron behaviors and its correlation with the microstructure and transport properties in Ce–Al(Ga) metallic glasses. It is expected that this study can provide some insights to understand the correlation between the microstructure and the transport behavior of Ce–Al (Ga) MGs.